1994
DOI: 10.2175/wer.66.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of macroinvertebrate communities from metal pollution in the South Fork and mainstem of the Coeur d'Alene River, Idaho

Abstract: zyxwvutsrqponmlkjihgfedcbaZYXWVUTSRQPONMLKJIHGFEDCBA Mining has severely impacted the biota in the Coeur d'Alene River drainage of northern Idaho. The benthic community of the South Fork and mainstem was monitored from 1968 to 1971 and from 1987 to 1991 to determine the effects of improved mine wastewater treatment and mine closures. With the decrease of heavy metal levels, the benthic community showed a gradual recovery as evidenced by large increases in taxonomic richness (0 to 18), EphemeropteraPlecoptera T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 14 publications
2
11
0
1
Order By: Relevance
“…Our results also are consistent with studies reporting rapid improvements in water quality and ecological condition over time or distance from stressor inputs (e.g., Poff & Matthews, 1986;Hoiland et al, 1994;Wellborn & Robinson, 1996;Adams & Greeley, 2000). For example, Sloane & Norris (2003) found that observed to expected ratios of macroinvertebrate occurrence increased with distance downstream of pollution from metal mines.…”
Section: Discussionsupporting
confidence: 92%
“…Our results also are consistent with studies reporting rapid improvements in water quality and ecological condition over time or distance from stressor inputs (e.g., Poff & Matthews, 1986;Hoiland et al, 1994;Wellborn & Robinson, 1996;Adams & Greeley, 2000). For example, Sloane & Norris (2003) found that observed to expected ratios of macroinvertebrate occurrence increased with distance downstream of pollution from metal mines.…”
Section: Discussionsupporting
confidence: 92%
“…Partial recovery of heavy metal polluted streams (Laurie and Jone, 1938;O'Grady, 1981) may follow cessation of mining activities provided that near-river spoil heaps are undisturbed. Further recovery is only achieved with active rehabilitation measures (Chadwick et al, 1986;Hoiland et al, 1994;Nelson and Roline, 1996;Watanabe et al, 2000) which may include tailings dams, settlement ponds or chemical treatment (Nuttall and Younger, 2000).…”
Section: Catchment Activitiesmentioning
confidence: 99%
“…Due to water-quality improvements in many of these streams with active or passive treatment systems in place, repopulation of stream biota, including macroinvertebrates and fishes, has occurred (Lacroix 1992;Hoiland et al 1994;Arnold and Gray 1998;Morris 2003). Traditional techniques for assessing stream restoration have been limited to water quality analysis, channel morphology and hydrologic assessment, qualitative or quantitative macroinvertebrate surveys, and fishery surveys.…”
Section: Introductionmentioning
confidence: 99%